THE EFFECT OF THE QUALITY OF PHARMACEUTICAL SERVICE ON OUTPATIENT SATISFACTION OF AMELIA HOSPITAL - Siahaan, Sahat Manampin; Hakim, Lukman; Hariyanti, Tita (Universitas Brawijaya, Indonesia, 2018)
This Research is expected to know the influence of the quality of services installation pharmaceutical a pharmaceutical, attitude officers, speed service, the provision of information and education medicine, and the availability of medicines of satisfaction outpatients at the hospital Amelia simultaneously, partial and the dominant. The results of the study can also be used as the basis in the arrangement the development program of increasing the quality of services pharmaceutical in conformity with expectation patients and renders service IFRS Amelia be an option to obtain medicine.The research is research observational analytic with the approach cross-sectional.Data analysis to research this using analysis linear regression multiple. The research results show that all dimensions the quality of services pharmaceutical influential together to satisfaction patients. Three dimensions speed service, the provision of information and education medicine and the availability of medicines influential be partial to satisfaction patients. Factors that dominant influential the quality of services pharmaceutical to satisfaction outpatients is a factor the availability of medicines.